Conflict and the Millennium Development Goals. - Stewart, F (2003)
Quand les riches se font la guerre ce sont les pauvres qui meurent Jean-Paul Sartre Le Diable et le Bon Dieu (1951) This paper reviews the effect of armed conflicts on development and, in particular, on the prospects of achieving the Millennium Development Goals. It explores the economic behaviour of countries affected by conflict and identifies the impact on different types of entitlement and in terms of human costs, particularly nutrition, health and education. It proposes a range of policy options that can be adopted towards countries at war.